Identifying novel strategies for treating human hair loss disorders : cyclosporine A suppresses the Wnt inhibitor, SFRP1, in the dermal papilla of human scalp hair follicles - Hawkshaw, Nathan J. (2018)
Hair growth disorders often carry a major psychological burden. Therefore, more effective human hair growth–modulatory agents urgently need to be developed. Here, we used the hypertrichosis-inducing immunosuppressant, Cyclosporine A (CsA), as a lead compound to identify new hair growth–promoting molecular targets. Through microarray analysis we identified the Wnt inhibitor, secreted frizzled related protein 1 (SFRP1), as being down-regulated in the dermal papilla (DP) of CsA-treated human scalp hair follicles (HFs) ex vivo. Therefore, we further investigated the function of SFRP1 using a pharmacological approach and found that SFRP1 regulates intrafollicular canonical Wnt/β-catenin activity through inhibition of Wnt ligands in the human hair bulb. Conversely, inhibiting SFRP1 activity through the SFRP1 antagonist, WAY-316606, enhanced hair shaft production, hair shaft keratin expression, and inhibited spontaneous HF regression (catagen) ex vivo. Collectively, these data (a) identify Wnt signalling as a novel, non–immune-inhibitory CsA target; (b) introduce SFRP1 as a physiologically important regulator of canonical β-catenin activity in a human (mini-)organ; and (c) demonstrate WAY-316606 to be a promising new promoter of human hair growth. Since inhibiting SFRP1 only facilitates Wnt signalling through ligands that are already present, this ‘ligand-limited’ therapeutic strategy for promoting human hair growth may circumvent potential oncological risks associated with chronic Wnt over-activation.